The Increased of Children Gross Motor Ability on Skipping at the Kindergarten - Jumareng, Hasanuddin; Asmuddin, Asmuddin; Saman, Abdul; Badaruddin, Badaruddin; Maruka, Aliasis (Universitas Negeri Semarang, 2021)
The purpose of this study was to increased of children rough motoric ability on skipping in kendari group B dharma wanita kindergarten. The subjects in this study were teachers and children in kendari group B kindergarten dharma wanita, which numbered 14 children consist of 7 boys and 7 girls with age range 5-6 years. In the results of pre-action observation, it was obtained that 14.28% or 2 of the 14 children were in good criteria for strength and balance, then first cycle increased to 71% or 10 of 14 children in good criteria and second cycle was 93% or 13 children from 14 the child is on the criteria for both strength and balance. In second cycle, the increase in the percentage of gross motor skills exceeds the success indicators set, namely 80% (12 children) of 14 children are in good criteria. Therefore, the learning in kendari group B kindergarten dharma wanita was said to be successful and the research was stopped. The children learning outcomes by rough motoric ability in the first cycle were achieved with a percentage of 64.29%, in the study there were 4 students obtain grouth by excellent with a percentage of 28.58%, 5 students received a grouth by expectation value with a percentage of 35.71%, 4 people students getting beginning to grouth values ​​with a percentage of 28.58%, and 1 students who getting just grouth values ​​with a percentage of 7.13%. In second cycle the teachers teaching activities obtained a percentage of 92.31% or as many as 12 aspects achieved from the 13 aspects observed, while those that unachieved were to 7.69% or 1 aspect that unachieved from the 13 aspects observed. Children's learning activities getting a percentage to 92.31% or as many as 12 aspects achieved from the 13 aspects observed while those that unachieved were to 7.69% or 1 aspect that unachieved from the 13 aspects observed. The children learning outcomes in increased of children rough motoric ability in the second cycle were achieved with a percentage of 92.9%, in the study there were 9 students who obtained grouth by excellent value with a percentage to 64.3%, 4 students obtained grouth by expectation value with a percentage to 28.6%, 1 students who get beginning to grouth values ​​with a percentage to 7.1% and no one who getting star developing values.